Analysis of Public Service Accountability at the Namlea Subdistrict Office, Buru Regency - Sitti Humayrah Galfia Djokja; Stanislaus Kostka Ohoiwutun; Ahmad Rosandi Sakir (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study aims to analyze public service accountability at the Namlea Subdistrict Office, Buru Regency. The research method used is qualitative, with an in-depth interview approach to gather information regarding the ongoing service processes at the subdistrict office. The research findings indicate that although some aspects of public service at the Namlea Subdistrict Office are running well, there are still areas that require improvement. The reporting process is relatively transparent, but it is hindered by a limited number of staff, which affects the timeliness of report resolutions. Information retrieval also relies heavily on direct visits to the office, suggesting the need for the implementation of information technology to make public access easier and more efficient. Service performance evaluations are conducted regularly, but they are constrained by staff capacity, which is insufficient to handle the volume of reports. Staff control and guidance are carried out routinely, but some members of the public seek increased transparency in this process. Overall, despite several challenges such as limited human resources and facilities, the Namlea Subdistrict Office has shown commitment to improving service quality. However, to enhance accountability, improvements are needed in transparency, information access, as well as strengthening staff capacity and the use of more advanced technology.